2013
DOI: 10.1186/1755-1536-6-20
|View full text |Cite
|
Sign up to set email alerts
|

Matrix regulation of idiopathic pulmonary fibrosis: the role of enzymes

Abstract: Repairing damaged tissues is an essential homeostatic mechanism that enables clearance of dead or damaged cells after injury, and the maintenance of tissue integrity. However, exaggeration of this process in the lung can lead to the development of fibrotic scar tissue. This is characterized by excessive accumulation of extracellular matrix (ECM) components such as fibronectin, proteoglycans, hyaluronic acid, and interstitial collagens. After tissue injury, or a breakdown of tissue integrity, a cascade of event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 96 publications
0
75
0
1
Order By: Relevance
“…Collagen 1a1 and fibronectin are the main components of ECM that participate in tissue and vascular remodeling. Increased collagen 1a1 and fibronectin expression is consistently associated with pulmonary fibrosis (29,30). We showed that treatment with ICG001 did not affect β-catenin nuclear translocation index but drastically downregulated cyclin D1, collagen Iα1, and fibronectin expression in CTGF transgenic lungs.…”
Section: Discussionmentioning
confidence: 73%
“…Collagen 1a1 and fibronectin are the main components of ECM that participate in tissue and vascular remodeling. Increased collagen 1a1 and fibronectin expression is consistently associated with pulmonary fibrosis (29,30). We showed that treatment with ICG001 did not affect β-catenin nuclear translocation index but drastically downregulated cyclin D1, collagen Iα1, and fibronectin expression in CTGF transgenic lungs.…”
Section: Discussionmentioning
confidence: 73%
“…IL-13 promotes fibrosis by stimulating collagen accumulation, downregulating MMPs and recruiting pro-fibrotic innate immune cells 83 . IL-13 also promotes the differentiation of fibroblasts into myofibroblasts and increases TGFβ expression 84 . How these cytokines and growth factors are upregulated in different tissues remains to be elucidated.…”
Section: Aberrant Ecm Remodelling In Diseasementioning
confidence: 99%
“…Thus, there is agreement that resident fibroblasts contribute to myofibroblasts in fibrosis, but the role of other cell types is controversial. The resident fibroblasts turn into myofibroblasts which produce excessive extracellular matrix components, especially collagen-I [10].…”
Section: Introductionmentioning
confidence: 99%